2015
DOI: 10.3844/ajavsp.2015.133.140
|View full text |Cite
|
Sign up to set email alerts
|

Closing the Gaps in Rat Cytomegalovirus ALL-03 (Malaysian Strain) Genomic Scaffold

Abstract: Next generation sequencing technologies has revolutionized genomic research by producing a large volume of sequence data and lowest per base cost compared to the traditional sanger method. Although this technology offers many advantages, gap occurrences are commonly found in draft assemblies. The same problem was observed with Rat Cytomegalovirus (RCMV) ALL-03 (Malaysia strain), where a complete genome sequence could not produce the complete genome due to the presence of gaps in the draft genome. This restrain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…This method is recommended for proper detection and identification of pathogens by using specific gene; hence this successful confirmation of positive cases by PCR agrees with [ 21 , 44 , 45 ] whom both in separate studies confirmed CE virus detection by using major genes essential for orf virus replication. An amplified gene product can be used as important genetic materials for further genetic analysis and gene expression studies [ 46 – 49 ] especially for their gene functions. This approach has been adopted for studies on other viruses such as herpes viruses, bacteria, and fungi (Balakrishnan et al, 2017 [ 50 ]).…”
Section: Discussionmentioning
confidence: 99%
“…This method is recommended for proper detection and identification of pathogens by using specific gene; hence this successful confirmation of positive cases by PCR agrees with [ 21 , 44 , 45 ] whom both in separate studies confirmed CE virus detection by using major genes essential for orf virus replication. An amplified gene product can be used as important genetic materials for further genetic analysis and gene expression studies [ 46 – 49 ] especially for their gene functions. This approach has been adopted for studies on other viruses such as herpes viruses, bacteria, and fungi (Balakrishnan et al, 2017 [ 50 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Whole Genome Sequencing (WGS) is now a common technique in contemporary plant research (Balakrishnan et al, 2015). WGS provides an opportunity to investigate nucleotide diversity much faster and more accurate than hybridization-based methods (molecular beacons, microarrays etc.…”
Section: Introductionmentioning
confidence: 99%